2023
DOI: 10.1002/alz.13507
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific genetic architecture of late‐life memory performance

Jaclyn M. Eissman,
Derek B. Archer,
Shubhabrata Mukherjee
et al.

Abstract: BACKGROUNDWomen demonstrate a memory advantage when cognitively healthy yet lose this advantage to men in Alzheimer's disease. However, the genetic underpinnings of this sex difference in memory performance remain unclear.METHODSWe conducted the largest sex‐aware genetic study on late‐life memory to date (Nmales = 11,942; Nfemales = 15,641). Leveraging harmonized memory composite scores from four cohorts of cognitive aging and AD, we performed sex‐stratified and sex‐interaction genome‐wide association studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Our findings from the sex-specific GWAS identified significantly associated SNPs on chromosome 2q (BIN1 locus) and 4q (QRFPR) for case-control ncAD in females only providing new insights into the gender-specific genetic basis for AD progression. In a recent sex-specific clinical GWAS for AD, BIN1 was also identified as having a female-specific association 28 . Another investigation, estimating hazard ratios, revealed that BIN1 contributes to a higher risk in females compared to males 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings from the sex-specific GWAS identified significantly associated SNPs on chromosome 2q (BIN1 locus) and 4q (QRFPR) for case-control ncAD in females only providing new insights into the gender-specific genetic basis for AD progression. In a recent sex-specific clinical GWAS for AD, BIN1 was also identified as having a female-specific association 28 . Another investigation, estimating hazard ratios, revealed that BIN1 contributes to a higher risk in females compared to males 29 .…”
Section: Discussionmentioning
confidence: 99%